Structural characteristics of er3+ and nd3+ doped lithium niobate tellurite glass - Hasim, N. (Trans Tech Publications Ltd, 2016)
Optimizing the rare earth doping in inorganic binary glasses for tuneable structural and optical properties is ever-demanding for lasing glass. A series of Er3+ and Nd3+ doped lithium niobate tellurite glasses with compositions of (70-x-y)TeO2–15Li2CO3–15Nb2O5–(x)Er2O3–(y)Nd2O3, where x = 0.0, 1.0 mol % and 0 ≤ y ≤ 1.0 mol% are synthesized using melt-quench technique. Influence of Nd3+ ion concentrations on physical and optical behaviour is examined. X–Ray diffraction pattern confirm the amorphous nature of glasses. The strong dependence of spectral properties on rare-earth dopant indicates the alteration in structures and bonding of glass network. The structural properties of the glass represented by the FTIR spectrum indicate that as Nd2O3 content increases, the sharp infrared absorption peaks are shifted from 474.7 cm-1 to 499.4 cm-1. These peaks are due to Nb-O, Te-O-Te and O-Te-O bond linkage bending vibrations. For TeO4 trigonal bipyramid, the peak occurred at 676.5 cm-1 whereas for TeO3 trigonal pyramid, two infrared band peaks are found at 787.5 cm-1 and 887.6cm-1, respectively. The absorption peaks around 1382.7 cm-1 is due to the Te-O-Nb stretching vibration while peaks at 1635.5cm-1 and 3411.7 cm-1 are due to the stretching vibrations of the hydroxyl group participating in the strong metal bonding as well as in the hydrogen bonding, respectively.